Micorrizas como bioindicador de la fertilidad de suelos en sistemas de producción de cacao del Cantón Buena Fé, Provincia de Los Ríos. - Reinoso Viteri, Dayanara Gabriela (2019)
Fertility diagnostic systems have been based on the determination of physical and chemical parameters excluding the biological aspects. In this work we talk about the mycorrhizae that are arbuscular fungi that benefit all plants for their innumerable functions, they also indicate that (measured through one or several of their structures) can be good indicators in terms of soil quality in our conditions. As a general objective, the soil fertility relationship was established with the presence of mycorrhizae in different production systems, evaluating the presence of mycorrhizae and fertility of cocoa soils, under agroecological, mixed and conventional production systems in the areas of El Triunfo, Congo and Cuatro Mangas del cantón Buena Fe. The research was carried out in the laboratory and greenhouse of Agricultural Innovation of the Maquita Foundation. A DCA design was used in factorial arrangement of 3 systems x 3 zones and 3 repetitions. For the fertility analysis, soil samples were taken in each production system and zone. Pots were used to plant sorghum and basil as trap plants whose roots are sensitive to mycorrhizal colonization. To stain the presence of mycorrhizae, the roots were stained and then observed under a microscope. With the results of soil analysis and the presence of mycorrhizae, radial diagrams were constructed to measure the influence of mycorrhizae on the nutritional load of the soils under study. The soil of the agroecological system of the area of Cuatro Mangas presented the highest percentage of colonization by mycorrhizae of the roots of the trap plants with 77%. Under the agroecological system the soil of the zone of Cuatro presented content of acceptable nutrients according to the fertility parameters in cocoa with (0.24%) of N, (10.3ppm) of P, (107.65ppm) of K, (1277.43ppm) ) of Ca, with Ph of 6.51 and organic matter with 5.82%. The highest biofertility index corresponded to the soil of the Cuatro Mangas area under the agroecological system, obtaining a high score with an average of 3.8 according to the scale of ideal parameters. Keywords: mycorrhizae, agroecological, production systems.